2019
DOI: 10.2134/jeq2019.04.0154
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Phosphorus Saturation as a Predictor of Redox‐Induced Phosphorus Release from Flooded Soils to Floodwater

Abstract: Abbreviations: DAF, days after flooding; DPS, degree of phosphorus saturation; DRP, dissolved reactive phosphorus; DRP max , maximum dissolved reactive phosphorus concentration in floodwater; Eh, redox potential; M3P MRP , Mehlich-3 extractable molybdate reactive phosphorus; M3P TP , Mehlich-3 extractable total phosphorus; PSI, phosphorus saturation index; STP, soil test phosphorus. D. Kumaragamage (ORCID iD 0000-0002-7613-0667),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…Unamended soil had a low DPS (10%) compared with SSM-and LSM-amended soils with DPS >35%, and in these amended soils, we observed a significant increase in floodwater DRP concentrations with decreasing pe + pH values with the progression of flooding. Results of the current study are consistent with the observation of Kumaragamage et al (2019) that the release of P in response to flooding is positively related to DPS.…”
Section: 4supporting
confidence: 92%
See 1 more Smart Citation
“…Unamended soil had a low DPS (10%) compared with SSM-and LSM-amended soils with DPS >35%, and in these amended soils, we observed a significant increase in floodwater DRP concentrations with decreasing pe + pH values with the progression of flooding. Results of the current study are consistent with the observation of Kumaragamage et al (2019) that the release of P in response to flooding is positively related to DPS.…”
Section: 4supporting
confidence: 92%
“…Previous studies investigating flooding-induced P release have shown a consistent and a substantial increase in pore water and floodwater DRP concentrations with time of flooding in most unamended soils with the exception of a few (Amarawansha et al, 2015;Jayarathne et al, 2016;Kumaragamage et al, 2019). The increase in DRP concentration with flooding and the development of anaerobic conditions have been attributed to pH changes resulting in enhanced solubility of phosphate minerals and the reductive dissolution reactions releasing adsorbed and precipitated P (Maranguit, Guillaume, & Kuzyakov, 2017;Rakotoson, Rabeharisoa, & Smolders, 2016;Weerasekara et al, 2020).…”
Section: Changes In Drp In Pore Water and Floodwater With Flooding Timementioning
confidence: 90%
“…This often reached a peak of around 21 to 42 DAF and then declined with further flooding time (Figure 1). Similar trends in pore water DRP concentrations have been reported for numerous soils with contrasting properties when packed soil mesocosms were flooded under warm temperatures (Amarawansha et al, 2015;Jayarathne et al, 2016;Kumaragamage et al, 2019). A notable difference between pore water DRP trends of previous studies with packed soil mesocosms conducted in the laboratory and in field and soil monoliths flooded in the current study is the sharper and more abrupt increase in pore water DRP concentration in soil monoliths in the current study corresponding to the immediate decrease in Eh following flooding.…”
Section: Changes In Pore Water Drp Concentration Under Two Flooding Csupporting
confidence: 80%
“…Anaerobic soil conditions resulting from prolonged flooding may enhance the release of soil P to overlying surface runoff water (Amarawansha, Kumaragamage, Flaten, Zvomuya, & Tenuta, 2015; Jayarathne, Kumaragamage, Indraratne, Flaten, & Goltz, 2016; Kumaragamage et al., 2019). It has been documented that anaerobic conditions even for periods of less than 20 d can enhance short‐term bioavailable P (Scalenghe, Edwards, Barberis, & Ajmone Marsan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A single point P sorption study was conducted by equilibrating a soil sample with a solution containing 150 mg P L −1 (Amarawansha, Kumaragamage, Flaten, Zvomuya, & Tenuta, 2016) and calculating the P sorption capacity using the difference between the initial and equilibrium solution P concentrations. The degree of P saturation was calculated by expressing Olsen P as a percentage of P sorption capacity (Amarawansha et al., 2016; Kumaragamage et al., 2019). Organic matter and calcium carbonate equivalent were also analyzed using a modified loss on ignition method (Dean, 1974).…”
Section: Methodsmentioning
confidence: 99%